The Pattern of Presentation of Abdominal Masses in Children - Wajeed Gul Bangash, Sher Zaman Khokhar, Asad Arif, Habib Ur Rehman, Feroze Ahmed Mahar, Aftab Ahmed Channa, (Pakistan Journal of Medical & Health Sciences, 2023)
Background; The abdominal masses in infants, neonate or child is a worrying sign that every clinician must be aware of as these masses can sometimes show malignant transformation. The outcome of this study would give an overview to the paediatric surgeons/ urologist about presenting spectrum of abdominal masses in children in our population which would enable them to manage these patients properly. Study Design: A Descriptive Cross-sectional Study conducted at Children Hospital, Shaheed Zulfiqar Ali Bhutto Medical University, PIMS Islamabad and Urology department of Islam Medical College/ Teaching Hospital, Sialkot for the duration of one year from January 2022 to December 2022. Material & Methods: This descriptive cross sectional study include ninety four (n=94) patients of less than 12 years of age irrespective of either gender who presented with abdominal mass. Patients suspected of having abdominal mass were screened from the outpatient (OPD) and emergency departments. Results; Out of 94 children, sixty five (69.15%) children were males whereas twenty nine (30.85%) were females. The male to female ratio was 2.24:1. Thirty five (37.33%) children were less than 1 year old, Twenty six (27.66%) were between age 1 and 3 years, nineteen (20.12%) children were between age 3 to 7 years and fourteen (14.89%) of children were elder than 7 years of age. The mean age was 7.4 months ± 2.1 Standard Deviation (SD). Most of the masses are benign and cystic in nature, however, Wilms’ tumour and neuroblastoma are two conditions that need a vigilant monitoring as these are the two malignant tumours (22.34% : n=21) in children where they usually present with abdominal mass. Conclusion; In a nutshell, any child presented with abdominal symptoms in surgical department must be investigated and managed accordingly. Any delay in diagnosis may cause fatal outcome. Keywords: Abdominal mass, UPJO-ureteropelvic junction obstruction, VUR (vesico-ureteric reflux), Hydronephrosis.